Music and adolescent identity - North, Adrian; Hargreaves, David (Routledge, 1999)
This paper reports four studies which investigated the function of musical preference as an identifying 'badge' by which adolescents express their own selfconcepts and make judgements of others. Studies 1 and 2 indicated that older and younger adolescents, respectively, hold normative expectations about the values and characteristics of fans of particular musical styles. Study 3 showed that 13-14- and 18-19-year-olds hold normative expectations which influence their perception of thelikely social consequences (e.g. having fewer friends) of being a fan of particular musical styles. The final study investigated hypotheses generated by the results of Studies 1-3. It demonstrated a positive relationship between adolescents' musical preference, self-concept, self-esteem, and normative expectations of the 'typical' fans of musical styles. This study also indicated that adolescents favour people who like the same musical style as they do, without necessarily denigrating those who do not. In conjunction, these studies provide empirical support for the notion that musical preference actsas a 'badge of identity' during adolescence, which predicts several other aspects of lifestyle and attitude.